2012
DOI: 10.2134/jeq2011.0131
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Produced from Anaerobically Digested Fiber Reduces Phosphorus in Dairy Lagoons

Abstract: This study evaluated the use of biochar produced from anaerobic digester dairy fiber (ADF) to sequester phosphorus (P) from dairy lagoons. The ADF was collected from a plugged flow digester, air-dried to <8% water content, and pelletized. Biochar was produced by slow pyrolysis in a barrel retort. The potential of biochar to reduce P in the anaerobic digester effluent (ADE) was assessed in small-scale filter systems through which the effluent was circulated. Biochar sequestered an average of 381 mg L P from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…In comparison, typically reported CEC values for soil components include <5 cmol c kg −1 for sand, <10 cmol c kg −1 for oxides, <15 cmol c kg −1 for Kaolinite, <150 cmol c kg −1 for smectite, and <250 cmol c kg −1 for bulk organic matter (OM) in soil (Brady and Weil 2008). Biochar has been reported to sorb dissolved ammonium (NH 4 + ) (Lehmann et al, 2002), nitrate (NO 3 − ) (Mizuta, 2004), phosphate (PO 4 3− ) (Beaton et al, 1960; Streubel et al, 2012), and other ionic solutes (Radovic, 2000) as well as hydrophobic organic pollutants (Accardi‐Dey and Gschwend, 2002; Gustafsson, 1997) from solution. Biochar derived from different biomass materials was shown to sorb phosphorus and nitrate from aqueous solutions (Emerson, 1921; Peech and English, 1943; Roller and McKaig, 1939; Sowden and Atkinson, 1949).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, typically reported CEC values for soil components include <5 cmol c kg −1 for sand, <10 cmol c kg −1 for oxides, <15 cmol c kg −1 for Kaolinite, <150 cmol c kg −1 for smectite, and <250 cmol c kg −1 for bulk organic matter (OM) in soil (Brady and Weil 2008). Biochar has been reported to sorb dissolved ammonium (NH 4 + ) (Lehmann et al, 2002), nitrate (NO 3 − ) (Mizuta, 2004), phosphate (PO 4 3− ) (Beaton et al, 1960; Streubel et al, 2012), and other ionic solutes (Radovic, 2000) as well as hydrophobic organic pollutants (Accardi‐Dey and Gschwend, 2002; Gustafsson, 1997) from solution. Biochar derived from different biomass materials was shown to sorb phosphorus and nitrate from aqueous solutions (Emerson, 1921; Peech and English, 1943; Roller and McKaig, 1939; Sowden and Atkinson, 1949).…”
mentioning
confidence: 99%
“…Studies have verified that biochar can act as an important carrier of organic pollutants (Chen et al, 2007) and heavy metals (Meena et al, 2005). Recent studies have also discussed the potential of biochar as a way of recovering nutrients from agricultural water such as dairy effluent (Streubel et al, 2012; Taghizadeh‐Toosi et al, 2012b). The term recovery is used here because the ultimate goal is to use biochar to sorb some of the nutrients from dairy effluent and apply the nutrient‐enriched biochar as a soil fertilizer.…”
mentioning
confidence: 99%
“…A number of researchers reported that biochar had little capacity for PO4 3-removal [6,12]. On the other hand, others reported that biochar has the capacity to remove or enhance phosphorus removal [4,5,7,13]. The apparently conflicting findings can be explained by the fact that the characteristics of biochar depend on the parent biomass and preparation conditions which affect their adsorption capacity of different chemicals [9,14].…”
Section: Ammonium Removalmentioning
confidence: 99%
“…Streubel et al (2012) demonstrated that biochar produced from anaerobic digester dairy solid fraction could be used to sequester P from dairy lagoons, through physical and weak chemical bonding, indicating that biochar could be a beneficial component to P reduction in dairy production systems. Biochar could also be blended with compost (Steiner et al, 2010) in order to retain NH 4 + and prevent NH 3 volatilisation, which could increase the value of the biochar once the compost is applied to soil.…”
Section: Biochar From Pyrolysis or Carbonisation Of Solid Manuresmentioning
confidence: 99%